Adequações proteicas em suplementos para bovinos em pastejo - Rocha, Pedro Ribeiro (2018)
The objective of this study was to evaluate the nutritional parameters of beef cattle grazing during the rainy-season transition period while receiving concentrate supplements containing two protein sources (soybean meal or distillers dried grains) formulated to meet 50% or 70% of the daily protein requirement. Five uncastrated Nellore steers with an average body weight (BW) of 356.6±14.56 kg were kept in individual paddocks of Uruchloa brizantha cv. Marandu grass in a 5×5 Latin square design arranged in a 2×2+1 factorial arrangement. The following supplements were evaluated: mineral mixture (control); and two protein sources (soybean meal - SM; distillers dried grains - DDG), which met 50% or 70% of the daily protein requirements for an estimated gain of 0.800 g/day. There was an increase (P<0.10) in intake and digestibility of DM, PDM, OM, CP, NDFap and DOM for the animals that received concentrate supplementation in relation to the control group. An interaction effect (P<0.10) between protein source and protein supply level was detected for the intake and digestibility values of DM, PDM, OM, CP, NDFap and DOM. The use of DDG meeting 70% of the daily protein requirement reduced the intake and digestibility of the evaluated nutrients. Concentrate supplementation for beef cattle grazing during the rainy-dry transition period increases the intakes of pasture and digestible organic matter; nitrogen retention; and microbial protein production. However, these variables are not increased when concentrate supplements containing soybean meal as the protein source are formulated to meet 70% of the crude protein requirement. Rather, supplying 70% of the crude protein requirement through supplements containing distillers dried grains has deleterious effects on those nutritional parameters.